Honesti et probi adolescentes. Pardon Letters and Student Violence at the Early Modern University of Louvain (Sixteenth-Seventeenth Centuries) - Gielis, Gert; Giraudet, Luke; Verreyken, Quentin (Students, Scholars and Their Books at the University of Louvain (1425-1797), 2026)
Ook in subreeks als Studium Lovaniense: Learning across Borders vol. 1

Studentenleven op de grens. Franse gratiebrieven voor studentengeweld in Leuven (1455) - Giraudet, Luke; Verreyken, Quentin (Lessen uit het verleden. Vier eeuwen studentennotities aan de Leuvense universiteit, 2025)